2015
DOI: 10.1002/jbmr.2766
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Repair in the Distal Radius in Postmenopausal Women: A Follow-Up 2 Years Postfracture Using HRpQCT

Abstract: Fracture healing is characterized by an intense increase in modeling and remodeling of bone, which allows removal of the cast after a stable distal radius fracture within 3 to 5 weeks. However, at that time, bone strength has not recovered yet. We studied the changes in bone mineral density (BMD), microarchitecture, and bone stiffness after a distal radius fracture during a 2-year follow-up in comparison to the contralateral side and the association between the 2-year stiffness and baseline BMD, microarchitect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 15 publications
(31 reference statements)
1
27
0
1
Order By: Relevance
“…Recently, HR-pQCT imaging made it possible to monitor the healing process of fractures by a non-invasive manner, as this technique identified differences in cortices and trabeculae during a follow up period of 2 years in the fractured and nonfractured site, whereas BMD was similar at both sites. 85 Moreover, a recent collaboration between different bone specialists showed that HR-pQCT imaging is a promising tool to define erosions in RA patients instead of using plane X-rays. 86 Another interesting observation is that HR-pQCT can measure changes in microarchitecture during treatment for a disease.…”
Section: Measuring Bone Strengthmentioning
confidence: 99%
“…Recently, HR-pQCT imaging made it possible to monitor the healing process of fractures by a non-invasive manner, as this technique identified differences in cortices and trabeculae during a follow up period of 2 years in the fractured and nonfractured site, whereas BMD was similar at both sites. 85 Moreover, a recent collaboration between different bone specialists showed that HR-pQCT imaging is a promising tool to define erosions in RA patients instead of using plane X-rays. 86 Another interesting observation is that HR-pQCT can measure changes in microarchitecture during treatment for a disease.…”
Section: Measuring Bone Strengthmentioning
confidence: 99%
“…Additionally, the osteoporosis was significantly reversed when the rats were fed the autophagy agonist rapamycin [18]. In a human study, the gene chip investigation from 984 volunteers showed that the autophagy-related gene (ATG) was the only statistically significant indicator associated with BMD in the distal radius [19]. These results all suggested that the autophagy signaling pathway played an important function in the pathogenesis of osteoporosis.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, it has been shown that the repair process of stable distal radius fractures can be monitored longitudinally in vivo using high-resolution peripheral computed tomography (HRpQCT) [ 6 , 7 ]. For clinical and research purposes, it would be of great interest to monitor the repair process of unstable fractures or the ingrowth of bone graft or bone graft substitutes after corrective osteotomy as well.…”
Section: Introductionmentioning
confidence: 99%